Anti-Myelin Oligodendrocyte Glycoprotein and Human Leukocyte Antigens as Markers in Pediatric and Adolescent Multiple Sclerosis: on Diagnosis, Clinical Phenotypes, and Therapeutic Responses. (22nd November 2018) - Gontika, Maria P.; Anagnostouli, Maria C.
Abstract : Early-onset (pediatric and adolescent) multiple sclerosis (MS) is a well-established demyelinating disease that accounts for approximately 3-5% of all MS cases. Thus, identifying potential biomarkers that can reflect the pathogenic mechanisms, disease course and prognosis, and therapeutic response in such patients is of paramount importance. Myelin oligodendrocyte glycoprotein (MOG) has been regarded as a putative autoantigen and autoantibody target in patients with demyelinating diseases for almost three decades. However, recent studies have suggested that antibodies against MOG represent a distinct clinical entity of dominantly humoral profile, with a range of clinical phenotypes closely related to the age of onset, specific patterns of disease course, and responses to treatment. Furthermore, the major histocompatibility complex (MHC)—which has been regarded as the "gold standard" for attributing genetic burden in adult MS since the early 1970s—has also emerged as the primary genetic locus in early-onset MS, particularly with regard to the human leukocyte antigen (HLA) alleles DRB1⁎1501 and DRB1⁎0401. Recent studies have investigated the potential interactions among HLA, MOG, and environmental factors, demonstrating that early-onset MS is characterized by genetic, immunogenetic, immunological, and familial trait correlations. In this paper, we review recent evidence regarding HLA-genotyping and MOG antibodies—the two most important candidate biomarkers for early-onset MS—as well as their potential application in the diagnosis and treatment of MS.